2022
DOI: 10.1088/1742-6596/2243/1/012062
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Study of Thorium Fuel Utilization on Small Modular Pressurized Water Reactors (PWR)

Abstract: Small Modular Pressurized Water Reactor (PWR) can be used to overcome the problem of electricity shortages in remote areas with fewer populations. These reactors usually use uranium-based fuel. Currently, the use of thorium-based fuels for this type of reactor has received constant attention, leading to several investigations of fuel performance. This study aims to determine the performance of thorium-based fuel in the PWR core at a power level of 300 MWt. The analysis was carried out by varying the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The SRAC system facilitates neutron calculations for different thermal reactors by generating accurate microscopic and macroscopic cross-sections. It supports core and static cell calculations, including burnup analysis, and provides essential parameters for reactor design and experimental analysis [27]. As a nuclear data library, we utilize JENDL 4.0.…”
Section: Calculation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SRAC system facilitates neutron calculations for different thermal reactors by generating accurate microscopic and macroscopic cross-sections. It supports core and static cell calculations, including burnup analysis, and provides essential parameters for reactor design and experimental analysis [27]. As a nuclear data library, we utilize JENDL 4.0.…”
Section: Calculation Methodsmentioning
confidence: 99%
“…The reactor core has three fuel regions (F1, F2, and F3) with a 1% 233 U content difference between each fuel region. F1 is the fuel region with the least fi ssile material, F2 is the fuel region with the medium fi ssile material, and F3 is the fuel region with the most fi ssile material [27]. The analyzed PWR design parameters are shown in Table 1.…”
Section: Reactor Designmentioning
confidence: 99%
“…2. The core configuration is designed by placing the fuel region with the lowest 233 U enrichment closest to the reactor core center (F1) and the fuel with the highest 233 U enrichment closest to the reflector (F3) [19]. As a result, F2 represents the fuel region with 233 U enrichment between F1 and F3.…”
Section: Fig 1 Fuel Cell Arrangementmentioning
confidence: 99%
“…Besides that, many studies have been conducted to investigate the performance of thorium-based fuel used in PWR. It has been shown that Th-232 and U-233 oxide or (Th,U-233)O2 fuel has excellent performance to a long-life PWR, those are longer operation period without refueling, higher internal conversion ratio, and higher fuel burn-up (Subki et al, 2008;Subkhi et al, 2012;Subkhi et al, 2013;Subkhi et al, 2015;Hassan et al, 2020;Napirah & Su'ud, 2020;Lapanporo & Su'ud, 2022).…”
Section: Introductionmentioning
confidence: 99%